2017
DOI: 10.1021/acs.oprd.6b00414
|View full text |Cite
|
Sign up to set email alerts
|

Amalgamation of Synthetic Biology and Chemistry for High-Throughput Nonconventional Synthesis of the Antimalarial Drug Artemisinin

Abstract: The development of a cost-effective process for the production of artemisinin, the precursor of all artemisininderived drugs, the first-line treatment for malaria, has been a long-pursued endeavor. The breakthrough achievement of coaxing genetically engineered yeast to express Artemisia annua genes for the commercial production of artemisinic acid, an advanced intermediate in the synthesis of artemisinin, has yet to fully realize an affordable malaria treatment for the poor because of the lack of a cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Singh et al showed a novel method of artemisinin production from amorpha-4,11-diene that can easily be commercialized due to its favorable route of synthesis [ 67 ]. In this method, functionalization of the isopropenyl moiety of amorphadiene through endo -epoxyamorphadiene produced dihydroartemisinic acid [ 67 ]. This pure dihydroartemisinic acid is esterified, oxidized and its final cyclization resulted in artemisinin in high yields [ 67 ].…”
Section: Increased Production Of Artemisinin and Its Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al showed a novel method of artemisinin production from amorpha-4,11-diene that can easily be commercialized due to its favorable route of synthesis [ 67 ]. In this method, functionalization of the isopropenyl moiety of amorphadiene through endo -epoxyamorphadiene produced dihydroartemisinic acid [ 67 ]. This pure dihydroartemisinic acid is esterified, oxidized and its final cyclization resulted in artemisinin in high yields [ 67 ].…”
Section: Increased Production Of Artemisinin and Its Analoguesmentioning
confidence: 99%
“…In this method, functionalization of the isopropenyl moiety of amorphadiene through endo -epoxyamorphadiene produced dihydroartemisinic acid [ 67 ]. This pure dihydroartemisinic acid is esterified, oxidized and its final cyclization resulted in artemisinin in high yields [ 67 ]. Some scientists have discovered short routes for the biosynthesis of artemisinin.…”
Section: Increased Production Of Artemisinin and Its Analoguesmentioning
confidence: 99%
“…Subsequently, Paddon and Singh et al described a commercially feasible and practical method for synthesis of artemisinin from amorpha‐4,11‐diene (Scheme 16). [49] The key to this novel approach is an exceedingly effective functionalization of the isopropenyl group of amorphadiene via endo epoxy amorphadiene to give dihydroartemisinic acid, which on esterification followed by oxidation and cyclicization furnishes pure artemisinin in the yield approximating 60 %. The isopropenyl group of amorphadiene was converted into endoepoxy product with H 2 O 2 .…”
Section: Biosynthesis Strategy For Artemisinin Synthesismentioning
confidence: 99%
“…Finally, very recently a route that differs in part from the previous approaches has been demonstrated. Chemists at IPCA have reported a novel large-scale synthesis of artemisinin from amorphadiene ( Singh et al, 2017 ). The key step in this route is the functionalization of amorphadiene using simple and cheap chemistry to directly afford ( R )-dihydroartemisinic acid (i.e., avoiding the need for a stereoselective reduction of artemisinic acid).…”
Section: Chemical Conversion Of Artemisinic Acid To Artemisininmentioning
confidence: 99%